Xanthones from Calophyllum inophyllum - Lee, Kar Wei; Ee, Gwendoline Cheng Lian; Daud, Shaari; Karunakaran, Thiruventhan (Universiti Putra Malaysia Press, 2017)
Repeated separation and purification of fractions from the crude chloroform extract of Calophyllum inophyllum via column chromatography afforded five known xanthone caloxanthones A, B, C, macluraxanthone and pyranojacareubin. Structural elucidations and determination of the isolated compounds were supported by spectral analyses obtained by subjecting the compounds to various spectroscopic techniques. The chloroform extract, when tested against RAW264.7 cells for anti-inflammatory potentials, exhibited the most promising activity with an IC50 value of 14.81±0.04 µg/mL compared to moderate activities shown by the ethyl acetate and n-hexane extracts. Antimicrobial tests showed that the n-hexane and chloroform extracts acted moderately against Staphylococcus epidermidis S273 and Bacillus subtilis B145.